Rapid fabrication of solid-state nanopores with high reproducibility over a large area using a helium ion microscope. Issue 11 (1st March 2018) - Xia, Deying; Huynh, Chuong; McVey, Shawn; Kobler, Aaron; Stern, Lewis; Yuan, Zhishan; Ling, Xinsheng Sean
Abstract : The practical issues (reproducibility, time and pore size control) for massive fabrication of nanopores over a wafer size of several inches for biomolecule detection are addressed here. Abstract : The fabrication of solid-state nanopores in an insulating membrane has attracted much attention for biomolecule analysis such as DNA sequencing and detection in recent years. For practical applications and device integration, the challenges include precise size control for sub 10 nm nanopores, excellent repeatability and rapid fabrication over a large area to reduce the cost for mass production. A helium ion beam could provide an effective fabrication approach to produce such solid-state nanopores. It is easy to control the nanopore size and reach sub 10 nm pore size with a simple change in the milling time with an appropriate ion beam current. Here we report new results in a set of experiments demonstrating that with a small range of stage automatized motions and equal mill times one can obtain good fabrication reproducibility in nanopore sizes (<10% variation in size). The automation in the stage motion and milling time opens a door for the rapid mass production of nanopore chips over a wafer size of several inches.